2021
DOI: 10.1136/bmjopen-2020-045795
|View full text |Cite
|
Sign up to set email alerts
|

Sibship size, birth order and risk of asthma and allergy: protocol for a systematic review and meta-analysis

Abstract: IntroductionThe hygiene hypothesis suggests that reduced exposure to microbes might have contributed to the increase in prevalence and incidence of asthma and allergy observed during the second half of the last century. Following this proposal, several studies have investigated the role of sibship size and birth order in the development of asthma and allergic diseases, but the underlying evidence is conflicting. The objective of the present systematic review will be to identify, critically appraise and synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Similarly, cases of allergic rhinitis may have been less accurately defined and/or identified in the studies that did not show a decreased risk, as indicated in the meta‐analysis on birth order and current allergic rhinitis, for which the 95% CI widened in a linear fashion in studies rated from “strong” to “weak,” with the pooled estimate from the “weak” studies indicating a nonsignificant association. Interestingly, sibship composition does not appear to have the same effect on the development of asthma, 66,67 suggesting differing underlying pathophysiological mechanisms 68 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, cases of allergic rhinitis may have been less accurately defined and/or identified in the studies that did not show a decreased risk, as indicated in the meta‐analysis on birth order and current allergic rhinitis, for which the 95% CI widened in a linear fashion in studies rated from “strong” to “weak,” with the pooled estimate from the “weak” studies indicating a nonsignificant association. Interestingly, sibship composition does not appear to have the same effect on the development of asthma, 66,67 suggesting differing underlying pathophysiological mechanisms 68 …”
Section: Discussionmentioning
confidence: 99%
“…We undertook this work following a protocol, which was registered on the International prospective register of systematic reviews (PROSPERO; CRD42020207905) and published 24 prior to undertaking the systematic review. The protocol was composed according to the Preferred Reporting Items for Systematic Review and Meta‐Analysis Protocols (PRISMA‐P) guidelines 25 .…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted according to an a priori published protocol [ 31 ], which was reported following the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) [ 32 ] and prospectively registered on the International Prospective Register of Systematic Reviews (PROSPERO; CRD42020207905). We reported our work in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) [ 33 ] checklist (supplementary table S1) and the Meta-analysis of Observational Studies in Epidemiology (MOOSE) [ 34 ] reporting guidelines (supplementary table S2).…”
Section: Methodsmentioning
confidence: 99%
“…This work was performed following a prospectively registered (International prospective register of systematic reviews [PROSPERO]; https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=207905) and published 26 protocol, based on the Preferred Reporting Items for Systematic Review and Meta‐Analysis Protocols (PRISMA‐P) guidelines 27 . Reporting of the present work was based on the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) 28 checklist (Supporting Information S1: Table E1) and the Meta‐analysis of Observational Studies in Epidemiology (MOOSE) 29 reporting guidelines (Supporting Information S1: Table E2).…”
Section: Methodsmentioning
confidence: 99%